Distinct non‐motor features of essential tremor with head tremor patients. (26th March 2020) - Peng, Jiaxin; Wang, Ling; Li, Nannan; Li, Junying; Duan, Liren; Peng, Rong
Abstract : Background: There have been few comprehensive scale studies on the non‐motor symptoms (NMS) of patients with essential tremor (ET) with head tremor (ETh) and those with ET without head tremor (ETol). We aimed to explore the motor symptoms and NMS of these two subgroups. Methods: We enrolled 199 patients with ET (125, ETol; 74 ETh) and 132 healthy controls. We evaluated motor symptoms using the Fahn‐Tolosa‐Marin Tremor Rating Scale (TRS) and NMS using the Non‐Motor Symptom Scale (NMSS). We compared NMSS scores and the prevalence of each NMS between the patient subgroups. Finally, we conducted a logistic regression analysis of the correlation between head tremor and NMS severity, as well as other determinants. Results: There were no significant between‐subgroup differences in demographic characteristics. Further, they presented similar tremor clinical manifestation; however, the ETh subgroup showed a higher prevalence of rest tremor, feeling of sadness, forgetting things or events, and swallowing difficulty, as well as TRS scores, compared with the ETol subgroup. Both patient subgroups showed high scores and prevalence (>50%) in difficulty falling asleep. Logistic regression analysis indicated age as a tremor severity determinant; further, head tremor and tremor severity were NMS determinants. Conclusion: Both patient subgroups presented various NMS including sleep disturbances, cognitive deficits, and affective disorders. The ETh subgroup showed a high prevalence of certain NMS aspects including memory and affective disorder; further, they had aggravated NMS. ET with both upper limb tremor and head tremor may be regarded as a more severe clinical subtype.